2019
DOI: 10.1093/ndt/gfz045
|View full text |Cite
|
Sign up to set email alerts
|

Excessive salt intake increases peritoneal solute transport rate via local tonicity-responsive enhancer binding protein in subtotal nephrectomized mice

Abstract: Background High peritoneal transport is associated with high mortality and technical failure in peritoneal dialysis (PD). Baseline peritoneal solute transport rate (PSTR) as measured by the peritoneal equilibration test (PET) within 6 months after PD initiation varies between patients. Sodium is reported to be stored in the skin or muscle of dialysis patients. This study investigated whether excessive salt intake in uremic mice caused peritoneal alterations without exposure to PD fluid. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…Interestingly, in the study by Sahinoz et al, higher plasma inflammatory markers (IL-6 and C-reactive protein) correlated with an increased muscle and skin sodium content [ 24 ]. This correlation heralds an interesting link between interstitial sodium and chronic inflammation, as already reported in experimental studies [ 26 , 27 , 28 ]. Thus, in nephrectomized rats, exposure to two weeks of higher salt intake increased the levels of IL-6, CMP-1, and TNF-alfa in the dialysate.…”
Section: Volume-independent Sodium Toxicity In End-stage Kidney Diseasesupporting
confidence: 71%
See 1 more Smart Citation
“…Interestingly, in the study by Sahinoz et al, higher plasma inflammatory markers (IL-6 and C-reactive protein) correlated with an increased muscle and skin sodium content [ 24 ]. This correlation heralds an interesting link between interstitial sodium and chronic inflammation, as already reported in experimental studies [ 26 , 27 , 28 ]. Thus, in nephrectomized rats, exposure to two weeks of higher salt intake increased the levels of IL-6, CMP-1, and TNF-alfa in the dialysate.…”
Section: Volume-independent Sodium Toxicity In End-stage Kidney Diseasesupporting
confidence: 71%
“…Finally, they reported that increasing the sodium intake induced an increase in peritoneal permeability (D/P creatinine increase). Each of these observed abnormalities reverted to normal after the sodium intake was reduced [ 26 ]. One notes that the results of this study [ 26 ] were consistent with findings from an early experiment on Winster rats showing that exposure to a higher sodium intake was associated with the thickening of the peritoneal membrane and peritoneal fibrosis as well as causing an epithelial-to-mesenchymal transition [ 27 ].…”
Section: Volume-independent Sodium Toxicity In End-stage Kidney Diseasementioning
confidence: 99%
“…Just as Li Han [20] believed that the Ccr of patients with low transport were not easy to reach 60L/1.73 m 2 , while its technical survival rate were not low but even exceed that of patients with high transport. A study from Japan [21] also demonstrated the value of high P/D Cr was also associated closely with higher mortality and failure of peritoneal dialysis. Our study compared different gender groups which suggested that the values of P/D Cr of male patients were higher than that of female patients on average, which was consistent with the ndings found by Lin tao [22] that male gender was a risk factor for high peritoneal transport status.…”
Section: Discussionmentioning
confidence: 92%
“…This finding is relevant because persistence of volume overload heralds a 60% higher mortality risk [84]. Interestingly, recent experimental findings have reported that high sodium intake is related to direct toxicity on the peritoneal membrane, leading to chronic inflammation, fibrosis, and hypervascularization, increasing, in turn, peritoneal permeability [86].…”
Section: Sodium Intake In End-stage Kidney Diseasementioning
confidence: 97%